Data set on wind speed, wind direction and wind probability distributions in Puerto Bolivar - Colombia - Guillermo Valencia Ochoa; José Núñez Alvarez; Marley Vanegas Chamorro (Data in Brief, 2019)
This paper presents wind speed and direction data measured with a weather station located in Puerto Bolivar, department of La Guajira, situated in the extreme north of Colombia, whose geographic coordinates are 12°11′N 71°55′W. A wind speed and direction sensor, a barometric pressure sensor, and a temperature sensor were used to obtain the presented data. These data were taken at the height of 10 m, which is the highest point of the weather station. The data taken by the meteorological station correspond to a period of 20 years (1993–2013), with hourly frequency. For the missing data, a mathematical model to estimate the Julian averages was developed, allowing to calculate the frequency histograms and four types of probability distributions for these data. Also, the representative wind roses were generated, taking into account the averages in each of the 12 months of the year. Keywords: Wind speed, Wind probability distribution, Wind direction